2006
DOI: 10.1111/j.1398-9995.2006.01174.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled formaldehyde exposure: effect on bronchial response to mite allergen in sensitized asthma patients

Abstract: Our study demonstrated that exposure to low levels of formaldehyde significantly enhanced bronchial responsiveness to mite allergen in mite-sensitized subjects with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 31 publications
1
51
0
3
Order By: Relevance
“…These products are produced locally in target tissues as well as systemically and they lead to widespread pro-inflammatory effects remotely from the site of the damage. The other mechanism suggests interactions between allergen and pollutants [140]. Some pollutants, in particular, diesel exhaust particles (DEPs), nitrogen dioxide, ozone and sulfur dioxide, could enhance airway responses to inhaled allergens.…”
Section: Potential Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…These products are produced locally in target tissues as well as systemically and they lead to widespread pro-inflammatory effects remotely from the site of the damage. The other mechanism suggests interactions between allergen and pollutants [140]. Some pollutants, in particular, diesel exhaust particles (DEPs), nitrogen dioxide, ozone and sulfur dioxide, could enhance airway responses to inhaled allergens.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…It has been shown that DEP, in synergy with allergens, could enhance allergen-specific IgE production by initiating a Th2 cytokine environment in the human upper respiratory mucosa. Recently, it has been shown that VOCs and formaldehyde could also have such interaction effects [133,140]. Only a few studies have evaluated the relationship between exposure to indoor pollution and asthma according to different phenotypes.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…Recent epidemiological studies have been conducted for investigating the interrelationship between FA exposure and asthma (Franklin et al, 2000;Youk et al, 2001;Rumchev et al, 2002;Gautrin et al, 2003;Vandenplas et al, 2004;Casset et al, 2006;Mi et al, 2006;Syamlal et al, 2009). Whether FA causes asthma is still under debate; there are only a few reports on FA and respiratory sensitization (Salthammer et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…38 However, in people with asthma and allergic sensitization to the dust mite Dermatophagoides pteronyssinus, inhalation of 100 µ/m 3 formaldehyde for 30 minutes caused a significant increase in bronchial responsiveness to the mite. 39 Associations between residential or school exposure to formaldehyde and respiratory symptoms has been reported in observational epidemiologic studies. 40,41 In a study that included 298 children and 613 adults in Tucson, Arizona, Kryzanowski and colleagues 40 reported that physician-diagnosed asthma and bronchitis, but not respiratory symptoms, were associated with increasing concentrations of formaldehyde.…”
mentioning
confidence: 99%